The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/term.1859
|View full text |Cite
|
Sign up to set email alerts
|

In-body tissue-engineered collagenous connective tissue membranes (BIOSHEETs) for potential corneal stromal substitution

Abstract: There is a severe shortage of donor cornea for transplantation in many countries. Collagenous connective tissue membranes, named BIOSHEETs, grown in vivo were successfully implanted in rabbit corneal stroma for in vivo evaluation of their suitability as a corneal stromal substitute to solve this global donor shortage. BIOSHEETs were prepared by embedding silicone moulds into dorsal subcutaneous pouches in rabbits for 1 month and stored in glycerol. After re-swelling in saline and trephining, disk-shaped BIOSHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…We have previously found that Biosheets produced by iBTA technology can recruit tissue stem cells from native tissue, and that these stem cells then mature and undergo proliferation (17). Biosheets were reconstructed in a manner analogous to native tissue, such as cornea, trachea, diaphragm, and esophagus (17,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that Biosheets produced by iBTA technology can recruit tissue stem cells from native tissue, and that these stem cells then mature and undergo proliferation (17). Biosheets were reconstructed in a manner analogous to native tissue, such as cornea, trachea, diaphragm, and esophagus (17,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…This technology has been successfully applied to the engineering of cardiovascular tissues, of vascular grafts as biotubes, or of heart valve-like tissues as biovalves. Biosheets, which are iBTA-induced membranous tissues, have been applied to the cornea [3], as well as to the repair of the diaphragm [4], esophagus [5], and trachea [6]. The studies that have reported on this technology indicated the possibility of tissue regeneration, self-repair, and growth adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has ushered in a new phase of regenerative medicine. 3 Grafts formed by iBTA can be made in any shape and form by suitably designed distributions of moulds; consequently, tubular connective tissue (biotube), 3 membranous tissue (biosheet), 4 and three dimensional valve shaped tissue (biovalve) 5 have been fabricated and transplanted in several animal models with satisfactory function.…”
Section: Introductionmentioning
confidence: 99%